Translation Techniques of Culture-Related Terms in The English Version of Eka Kurniawan’s Novel: Seperti Dendam, Rindu Harus Dibayar Tuntas - Ridho Wasisto; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Translation process and translation products can not be separated from literature and culture in the current age of information. Problems can occur when translating cultural elements, especially in literary works. This research aims to identify culture-related terms and the translation techniques used to translate them in the english version of Eka Kurniawan’s novel: Seperti Dendam, Rindu Harus Dibayar Tuntas. An alternative categorization of culture-related terms is introduced to improve the scope of analysis. This is a descriptive contrastive translation study with purposive sampling method being used for the data gathering. The results show that the most frequent categories of culture-related terms in the ST are Idioms, Work and Leisure, Flora and Fauna, Food and Drink, and Tools and Techniques. These top five categories account for 55% of all the culture-related terms in the ST. The result also shows that the most dominant translation techniques are the Established Equivalent and the Literal Translation, which account for 51.2% of all the data. This shows that around half of the culture-related terms found in the ST have their equivalent words in the TL. However, some data shows that Literal Translation is not always a reliable technique, especially when translating Idioms. When translating culture-related terms without equivalence, other frequent techniques shown in the result are: Borrowing, Adaptation, Description, and Amplification.